DDEL-03. The use of programmable valves as a vehicle for intrathecal chemotherapy delivery in infants with CNS tumors and hydrocephalus. (3rd June 2022) - Dvir, Rina; Rosenberg, Tom; Elhasid, Ronit; Levin, Dror; Constantini, Shlomi; Roth, Jonathan
Abstract: INTRODUCTION: Current chemotherapy protocols for treatment of embryonal brain tumors in infants recommend administration of intrathecal chemotherapy either by a lumbar tap or via an Ommaya reservoir. Children with concurrent hydrocephalus and shunts may have sub-therapeutic levels of chemotherapy in the CSF due to constant CSF drainage to extra-CNS compartments. We present our experience in delivery of chemotherapy to young children via programmable valves. RESULTS: A retrospective analysis of infants with CNS malignancies and hydrocephalus treated with a shunt and a programmable valve (CERTAS™ Plus Programmable Valves - Integra Life Sciences) was conducted. Five infants 1.1-3 years of age (mean 2) were included. Pathologies included atypical teratoid rhabdoid tumor (ATRT N=2), medulloblastoma (N=2), and metastatic rhabdomyosarcoma(N=1). Intrathecal injections were conducted in an outpatient setting unless hospitalization was required for other reasons. Only one child required sedation due to noncompliance. A total of 61 chemotherapeutic administrations were performed directly through the valve while set on an extremely high opening pressure for several hours( 35 with hydrocortisone and cytarabine, 26 with topotecan). There were no infections, leaks or major complications. One child required a wound revision due to exposure of the proximal catheter related to extremely thin skin, one child developed somnolence and fever which were not related to a shunt malfunction or infection, and one child had clinical and radiological shunt over-drainage solved by increasing of valve settings. CONCLUSIONS: Programmable ventriculoperitoneal valves appear to a safe method for delivery of chemotherapy in infants with malignant CNS tumors .This technique may potentially have an added value for children with concurrent shunts, and may also obviate the need for an additional ventricular access device .